Survey on secure protocols for data sharing through edge of cloud assisted internet of things - Sai Prasanthi, K; V.Daya Sagar, K (International Journal of Engineering and Technology, 2018)
Nowadays Internet of Things (IoT) is the trending topic where we go. IoT is included in almost every device surrounded by us where valuable information is shared over the network to store it in the cloud or to transfer as a message alert to an individual. IoT devices generate a huge amount of data but only caring information is required and for that analytics needs to be performed. Analytics are reaching outside of the traditional datacenter towards the edge, where the IoT data is generated. So, here in this paper, the importance of secure data sharing over a network, generated by IoT devices is described and along with that the data flow between IoT and edge server is discussed, and the requirement of edge analytics is focused.